High Performance Liquid Chromatography-Mass Spectrometry for Determination of Benzo[a]pyrene in Grilled Meat Foods - Ince, Muharrem; Yaman, Mehmet (Asian Journal of Chemistry, 2012)
The concentrations and varieties of benzo[a]pyrene were determined in Turkish foodstuffs including grilled meat and chicken samples by high performance liquid chromatography-mass spectrometry (HPLC-MS). The parameters that are thought to affect the response in the HPLCMS analysis were optimized. The optimized conditions were found to be 0.75 mL min-1 for flow rate of mobile phase, 45 μL for injection volume, 55 ºC for column temperature and 140 V for fragmentor potential. The optimized method was applied for the determination of benzo[a]pyrene concentrations in grilled meat and chicken foods. The obtained concentrations were found in the range of 2.7-8.3 μg kg-1 for the normal grilled meat and chicken samples and 72-138 μg kg-1 for over-grilled samples. The results showed that the concentrations of benzo[a]pyrene were significantly dependent on the kind of meat and the cooking time and source. The limits of detection and quantitation were found to be 0.7 and 2.33 μg L-1, respectively.